The Prudential Principle of Land Deed Official in Drafting Agreement: Minors Protection and the Role of the Orphans Chamber - Pati, Sakka; Miru, Ahmadi; Marwah, Marwah; Yunus, Ahsan; Yasin, Rifky Adam (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Land Deed Officials are required to act diligently and professionally, adhering strictly to the principle of prudence when preparing sale and purchase deeds, particularly those involving property owned by minors. According to the Indonesian Civil Code, guardians must notify the Orphans Chamber (Balai Harta Peninggalan) and conduct the transaction in the presence of a supervising guardian when selling immovable property belonging to minors. However, in practice, such transactions often bypass the Orphans Chamber, raising legal concerns due to the potential for guardians to misuse the proceeds from the sale. This study explores how Land Deed Officials implement the prudential principle in drafting deeds for the sale of minors' property. Using qualitative methods, the research analyzes relevant legal frameworks, sale documents, and interviews with Land Deed Officials, Orphans Chamber representatives, and guardians. The findings reveal that the application of prudence by Land Deed Officials remains suboptimal. Many rely solely on court decisions authorizing parental guardianship, overlooking the legally mandated role of the Orphans Chamber in safeguarding the interests of minors. The study underscores the critical need for supervisory oversight to ensure the protection of children’s rights in property transactions.